2019
DOI: 10.3345/kjp.2018.06744
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal midline cutaneous stigmata associated with occult spinal dysraphism in pediatric patients

Abstract: Purpose To investigate the prevalence of occult spinal dysraphism (OSD) and subsequent neurosurgery in pediatric patients with isolated or combined dorsal midline cutaneous stigmata with or without other congenital malformations. Methods We carried out a retrospective review of patients who underwent sonography or magnetic resonance imaging (MRI) for OSD because of suspicion of dorsal midline cutaneous stigmata (presumed to be a marker for OSD) between January 2012 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…The prevalence of OSD was significantly higher in patients with combined stigmata (10.5%) than those with a single stigmata (2.3%). This finding is consistent with the results of previous studies that reported that a combination of 2 or more midline cutaneous lesions is more likely to be associated with OSD than a single lesion . Therefore, when evaluating infants with dorsal midline skin lesions, meticulous screening for skin lesions is warranted to determine whether 2 or more lesions are present, given that this indicates a higher risk of OSD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of OSD was significantly higher in patients with combined stigmata (10.5%) than those with a single stigmata (2.3%). This finding is consistent with the results of previous studies that reported that a combination of 2 or more midline cutaneous lesions is more likely to be associated with OSD than a single lesion . Therefore, when evaluating infants with dorsal midline skin lesions, meticulous screening for skin lesions is warranted to determine whether 2 or more lesions are present, given that this indicates a higher risk of OSD.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the results of previous studies that reported that a combination of 2 or more midline cutaneous lesions is more likely to be associated with OSD than a single lesion. 25,26 Therefore, when evaluating infants with dorsal midline skin lesions, meticulous screening for skin lesions is warranted to determine whether 2 or more lesions are present, given that this indicates a higher risk of OSD. However, some studies in our current review focused on specific skin lesions, such as spinal strawberry nevi 5 and dorsal midline vascular anomalies, 8 that are associated with other stigmata.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings concur with previous studies that >1 LsCM portends a significantly higher risk of OSD than a single LsCM. 3,1012…”
Section: Discussionmentioning
confidence: 99%
“…[6] Penelitian melaporkan bahwa jika ditemukan stigmata kulit di garis tengah punggung, misalnya massa fibrofatty, lesung kulit di daerah sakral, aplasia kulit, dan hipertrikosis maka perlu diwaspadai adanya SB okulta, terutama jika terdapat kelainan kongenital lainnya. [7] Spina bifida aperta (SBA) disebut juga SB cystica, saat lahir terlihat sebagai jaringan saraf yang terbuka dengan atau tanpa kantung yang menonjol di lokasi lesi. SBA dapat berupa myeloschisis atau myelomeningocele.…”
Section: Etiologiunclassified